Dinosaur tracks : the next steps - Falkingham, Peter L.; Marty, Daniel, 1973-; Richter, Annette (Life of the past., 2016)
"This book was developed from a dinosaur track symposium that was organized and held in April 2011 in Obernkirchen, Germany, on behalf of the Niedersachsisches Landesmuseum Hannover (Lower Saxony State Museum Hannover)."--